2014
DOI: 10.1038/hdy.2014.58
|View full text |Cite
|
Sign up to set email alerts
|

Footprints of divergent selection in natural populations of Castanopsis fargesii (Fagaceae)

Abstract: Given predicted rapid climate change, an understanding of how environmental factors affect genetic diversity in natural populations is important. Future selection pressures are inherently unpredictable, so forest management policies should maintain both overall diversity and identify genetic markers associated with the environmental factors expected to change most rapidly, like temperature and rainfall. In this study, we genotyped 648 individuals in 28 populations of Castanopsis fargesii (Fagaceae) using 32 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…Our results revealed a pattern of genetic divergence similar to that shown in Castanopsis fargesii [34]. The authors proposed that the rapid and dramatic uplift of the western Yunnan-Guizhou plateau and the eastern Wuyi Mountains had a huge impact on the molecular differentiation of the subtropical broad-leaved tree species in China.…”
Section: Genetic Structure Analysis Of T Ciliatasupporting
confidence: 77%
“…Our results revealed a pattern of genetic divergence similar to that shown in Castanopsis fargesii [34]. The authors proposed that the rapid and dramatic uplift of the western Yunnan-Guizhou plateau and the eastern Wuyi Mountains had a huge impact on the molecular differentiation of the subtropical broad-leaved tree species in China.…”
Section: Genetic Structure Analysis Of T Ciliatasupporting
confidence: 77%
“…Castanopsis carlesii is distributed over a large geographical range throughout subtropical China, and substantial differences in characteristics of precipitation and temperature were obvious across this area (Li et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This is also confirmed by the DIY ABC analysis that suggested the existence of recurrent gene flow between these varieties. Widespread and abundant gene flow has been revealed in natural populations of other Castanopsis species, maintaining high diversity while diversifying selection was acting on specific genomic regions (Li et al 2014). Differential adaptation to natural environment can drive phenotypic divergence of population, and simulations showed that even weak selection for local adaptations could cause highly divergent clades geographically localized (Irwin 2012).…”
Section: Adaptation and Divergence With Gene Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Although microsatellites are frequently presumed to be neutral because they are not transcribed or translated, they can be linked to functional genes under selection (e.g. Vasemagi et al 2005;Li et al 2014) or may be involved in DNA folding (Li et al 2002). SNPs can be influenced by either neutral or adaptive genetic processes and can represent functional, coding regions of the genome, which on the one hand are under purifying selection to avoid deleterious changes and on the other under positive selection for advantageous changes.…”
Section: Introductionmentioning
confidence: 99%